Impaired Object Handling during Bimanual Task Performance in Multiple Sclerosis. (11th August 2014) - Gorniak, Stacey L.; Plow, Matthew; McDaniel, Corey; Alberts, Jay L.
Abstract : We investigated the kinetic features of manual dexterity and fine motor control during a task that resembles an activity of daily living in 30 persons with relapsing-remitting multiple sclerosis (PwMS). Specifically, a novel two-transducer system was used to measure time and grip-load forces during a bimanual task that is similar to opening and closing a jar. We hypothesized that PwMS would have increased grip force production, deteriorations in kinetic timing, and preserved grip-load coupling indices compared to healthy controls (i.e., young and older adults). Increased grip force production and deterioration in timing indices were confirmed in PwMS. Abnormal grip-load coupling was exhibited by PwMS, in contrast to healthy participants. The correlation between task time and self-reported disability scores suggests that objective measurement of impaired upper-extremity movements relates to perception of overall function.